The process of lending and analysis of the credit market in the domestic banking sector in the digital economy - Isanov, A.S.; Sembekov, A.K.; Toleuuly, А.; Dzhumabaeva, Sh.B.; Kuldeeva, A.T (BUKETOV BUSINESS REVIEW, 2023)
Object: The content of the credit market is still not deeply studied. The differentiated approaches of economists to the definition of the credit market indicate that its content is theoretically insufficiently studied and further study of this phenomenon is necessary. The purpose of the research of the article is to determine the objective laws of the development of the credit market, promising directions for its modernization and increasing its role in the national economy on the basis of a scientifically based concept. Methods: During the research, the methods of scientific abstraction, gradual transition from the abstract to the concrete, typology, induction, deduction, analysis, synthesis, historical and logical unity, modeling and other methods of scientific cognition were used. To reveal the content of the credit market, methods of scientific abstraction were used, a gradual transition from the abstract to the real, on the basis of which the credit market was studied as a kind of economic category “market”, the real product of which are credit products. This made it possible to determine its significance, functions, role, and reveal the patterns of development of the credit market. On the basis of such methods of scientific knowledge as historical and logical unity, analysis and synthesis, the main stages and trends in the development of the credit market are determined, the directions of its modernization are determined. Findings: As a result of the monetary policy in the third quarter of 2022, the cost of credit resources increased. Nevertheless, the volume of lending to legal entities continued to grow mainly due to the provision of loans to businesses in tenge. Despite the decline in credit activity and the deterioration of logistics of banks previously affected by the sanctions imposed on Russia, there is a positive growth in the issuance of loans in the main sectors of the economy (trade, construction, transport and agriculture). Conclusions: The economy of Kazakhstan needs dynamic sustainable development, which can be ensured, in particular, due to a successfully functioning credit market. For a long time, the credit market has not been the subject of special fundamental research in terms of the patterns and proportions of its development, which significantly worsened its knowledge and narrowed the possibilities of its application for the purposes of National economic growth. In the dissertation research, for the first time, objective patterns of the development of the credit market have been identified, which form the basis of a scientifically based concept as a contribution to solving this problem and determine the promising directions of its modernization in order to increase the role of the credit market in the national economy.